Low-autofluorescence fluoropolymer membrane filters for cell filtration. (24th May 2018) - Kihara, Naoto; Kuboyama, Daiki; Onoshima, Daisuke; Ishikawa, Kenji; Tanaka, Hiromasa; Ozawa, Naoya; Hase, Tetsunari; Koguchi, Ryohei; Yukawa, Hiroshi; Odaka, Hidefumi; Hasegawa, Yoshinori; Baba, Yoshinobu; et al.
Abstract: A fluoropolymer membrane filter with through-holes was fabricated by photolithographic patterning and the dry etching method. 380, 000 highly packed through-holes, each with a diameter of 7 µm were able to cover a whole area with a diameter of 13 mm. Ethylene tetrafluoroethylene (ETFE) was used as the membrane, which was suitable for the fluorescence detection of rare cells such as circulating tumor cells (CTCs) in human blood. The device fabrication for the size based capture of rare cells in blood such as CTCs is realized in this study.